STRATEGI ANALISIS STRATEGI PEMASARAN PADA KINERJA PEMASARAN PT. GREENTECH CAKRAWALA MOTORINDO - Maulana Rezfajri S; Jenny Susanti; Fitri Yani; Bord Nandre Aprila (Institut Bisnis dan Teknologi Pelita Indonesia, 2022)
The automotive industry is an industrial sector that can support the income and economic growth of the country. Then the automotive industry sector became important for the Countries of the world. Seeing this phenomenon, countries in this world compete with each other to distribute automotive, especially in motorcycles which in terms of price are more affordable by the public. In the process of collecting data, the author uses observation techniques, namely by making direct observations on employment from the process of observing marketing strategies in offering Kawasaki motorcycle products to PT. Greentech Cakrawala Motorindo. Based on the company's internal and external analysis along with the cartesius diagram, it can be concluded that what makes the main strategy in PT. Greentech Cakrawala Motorindo is a development strategy (growth). Can develop effective distribution channels by prioritizing product quality, especially on Kawasaki brand motorcycles by developing the abilities of workers and utilizing good promotions, especially on social media. Alternative strategies obtained, the most appropriate strategy used by PT. Greentech Cakrawala Motorindo in order to continue to increase sales, namely the formulation of an effective strategy finally obtained is the SO strategy, which is a strategy by using Strength to utilize opportunies owned by the company Based on the SWOT matrix, it can be concluded that several developments through consideration of internal and external factors of the company that can be beneficial for the progress of PT. Greentech Cakrawala Motorindo.